Membangun Generasi Berkarakter melalui Tiga Pilar Budaya Sekolah: 5S, Religius, dan Literasi di SDN Merjosari 2 - Moh Rrizky Ardanyansyah; Putri Alfiyah; Nawa Nasikhatul Milah; Shobihatul Fitroh Noviyanti (Al-Kindi, 2026)
This study aims to examine the implementation of the three pillars of the 5S school culture (Smile, Greeting, Greeting, Politeness, Courtesy), religious, and literacy, and its impact on the character formation of students at SDN Merjosari 2. The method used is descriptive qualitative with data collection techniques in the form of observation and in-depth interviews with the principal, the vice-curriculum supervisor, and the homeroom teacher. The results of the study indicate that the 5S culture implemented through the habit of greeting, shaking hands, and being friendly successfully changes student behavior to be more polite and disciplined. Religious culture includes alternating dhuha prayers between classes, congregational zuhur prayers, Qur'an tartil, and joint prayers, which increase students' responsibility for worship. Literacy culture is realized through class reading corners, Wednesday storytelling activities, and group discussions, which not only improve reading skills but also students' courage to speak and express opinions. Evaluation of success is carried out through violation records and regular homeroom teacher meetings. Obstacles found include differences in family backgrounds and peer influence. Overall, the three pillars of school culture at SDN Merjosari 2 effectively build a generation with superior character in terms of politeness, religiosity, and literacy.